Rethinking global governance - Weiss, Thomas G. (Thomas George) 1946-; Wilkinson, Rorden 1970-
Rethinking Global Governance casts fresh eyes upon a once poignant but now languishing concept. Its purpose is to disrupt the simple association between global governance and the actions and activities of international organizations in the post-Cold War era and to focus instead on a set of questions that probe the intricate and multifaceted manner in which the world is governed. The book moves beyond the ubiquity and imprecision that has plagued the term and offers an intellectual framework with the potential to improve both thinking and practice.